2014
DOI: 10.1371/journal.pone.0099154
|View full text |Cite
|
Sign up to set email alerts
|

School Social Fragmentation, Economic Deprivation and Social Cohesion and Adolescent Physical Inactivity: A Longitudinal Study

Abstract: ObjectivesTo examine the independent influence of school economic deprivation, social fragmentation, and social cohesion on the likelihood of participating in no physical activity among students.MethodsData are from a large-scale longitudinal study of schools based in disadvantaged communities in Quebec, Canada. Questionnaires were administered every year between 2002 and 2008 among n = 14,924 students aged 12 to 18 from a sample of 70 schools. Cross-sectional and longitudinal analyses were conducted. Multilev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 43 publications
1
13
0
1
Order By: Relevance
“…61,6567 Our finding that from crude to adjusted models, only the highest level of informal social control and political participation remained associated with the outcome suggests that income inequality and social fragmentation may confound the relationship by both eroding social capital 32,45 and delaying HIV diagnoses.…”
Section: Discussionmentioning
confidence: 85%
“…61,6567 Our finding that from crude to adjusted models, only the highest level of informal social control and political participation remained associated with the outcome suggests that income inequality and social fragmentation may confound the relationship by both eroding social capital 32,45 and delaying HIV diagnoses.…”
Section: Discussionmentioning
confidence: 85%
“…Accessibility to sports fields and gyms, as well as the presence of equipment and a welcoming and safe environment promote physical activity in the school environment [32]. A systematic review [12] found that physical activity interventions in these conditions reduce body mass index (BMI) and that regular practice represents an important change in nutritional status in the school population.…”
Section: Discussionmentioning
confidence: 99%
“…A random sample of 40 schools with more than 90 students enrolled in fifth grade was identified from among all French language schools in greater Montreal. To assure equal representation of students of high, middle, and low socioeconomic status (SES), schools were stratified into groupings defined by tertiles of an indicator [17] based on maternal education, parental employment, and a measure of low family income that accounts for family size and area of residence [18,19]. An equal number of schools were selected into each grouping, and 29 schools (72.5% of those invited), including 10 in the first, 10 in the second and nine in the third groupings, agreed to participate.…”
Section: Methodsmentioning
confidence: 99%